Synthesis and characterization of new azaheterocyclic aromatic phosphonates for hybrid materials for fuel cell applications - Teixeira, Fatima (2020)
ABSTRACT: This work reports the synthesis and characterization of new azaheterocyclic aromatic phosphonates derivated from benzimidazole and benzotriazole by nickel-catalyzed Arbuzov reaction of 4,7-dibromo-2,1,3-benzothiadiazole with triethyl phosphite, followed by reductive sulfur extrusion reaction and cyclization. The compounds were characterized by NMR and mass spectrometry (low and high resolution). These azoles will be incorporated into proton conductive inorganic-organic hybrid membranes of mesoporous silica to produce novel membranes materials with high proton conductivity for intermediate temperature PEMFCs.